Computer Modeling and Integrated Forming Technologies - Chukhlib, Vitalii; Biba, Nikolay; Zakovorotniy, A.; Duvanskyi, Oleksandr; Paliienko, Volodymyr (ISMA University of Applied Science, 2021)
The genesis of the view on the content of the modern development of education in the field of computer modeling and integrated technologies of forming is considered. The analysis of the current state of training of specialists at the Department of Computer Modeling and Integrated Forming Technologies of the National Technical University "Kharkiv Polytechnic Institute", as well as possible directions of scientific work at this department.
Keywords: computer modeling; integrated; forming technologies